Structurally different short aramid fiber–reinforced thermoplastic polyurethane. Issue 9 (28th December 2013) - Shibulal, G.S.; Naskar, K.
<x xml:space="preserve">Abstract</x> The reinforcing effect of two structurally different Aramid short fibers, Technora and Twaron on the mechanical, dynamic mechanical, and thermal properties of an ester‐based thermoplastic polyurethane (TPU) was investigated. A fixed fiber length of 6 mm is used by varying the fiber loading ranging from 3 to 10 phr. The Young's modulus and the low strain modulus of Technora–TPU composite was found three times higher than that of Twaron–TPU composite at all ranges of fiber loading. Optical microscopic analysis revealed that a severe processing‐induced fiber breakage of Twaron is the primary reason behind the inferior properties shown by these fiber‐reinforced TPU composite. A brittle kind of failure has been observed during tensile testing in both the composite at a fiber loading of 10 phr. To solve this problem, an economic pretreatment with maleic anhydride‐grafted polybutadine (PB‐g‐MA) has been applied on the Aramid fiber surface before mixing it with the TPU matrix. A good quality of fiber dispersion with significant improvement in mechanical properties could be achieved with the addition of only 5 phr of PB‐g‐MA. Morphological analyses on the tensile‐fractured and cryogenically fractured surfaces of these composites offer strong evidences for the dispersing and coupling action of PB‐g‐MA with these Aramid fibers and the TPU matrix. POLYM. COMPOS., 35:1767–1778, 2014. © 2013 Society of Plastics Engineers